Development of STEM-based E-LKPD to improve scientific literacy capabilities on environmental change material - Suci Fitria; Ahmad Sofyan; Eva Fadilah (EDUSAINS, 2025)
The problem of low science literacy needs to be used as a reference by the government in improving the learning system in Indonesia. This research aims to produce teaching materials in the form of STEM-Based Electronic Student Worksheets (E-LKPD) to Improve Science Literacy Skills in Environmental Change Materials. The method used is Research and Development (R&D) with a 4-D development model (Define, Design, Develop, and Disseminate). The development process goes through a validity test of 2 experts, a readability test of 15 students, and a field trial by 1 biology teacher and 35 students. Pretests and posttests were conducted using multiple-choice test instruments consisting of the same 10 questions. The results of the research showed that the developed E-LKPD had an average validity percentage of 85.2% with very feasible criteria. In the readability test, the average percentage of E-LKPD reached 86.2% with very feasible criteria. While in the field trial, the responses of teachers and students showed very feasible criteria with percentages of 81.25% and 82.25%. There was an increase in the average scientific literacy skills measured through the test instrument. The average result of scientific literacy skills before the implementation of E-LKPD was 57.3 while after the implementation of E-LKPD it increased to 79.6 with an N-Gain of 0.50 in the moderate category. Based on these results, it can be concluded that E-LKPD is very feasible to use in learning activities and there is an increase in scientific literacy skills after the use of E-LKPD in the learning process.